Stainless steel coated by Cu NPs via dopamine coupling for antifouling application. (29th May 2019) - Cao, Pan; Cao, Zhimin; Yuan, Chengqing
Abstract : Biofouling is very harmful in diverse industries. Copper nanoparticles (Cu NPs) possess excellent antifouling performances. In this study, in situ generation of Cu NPs on dopamine modified 304 stainless steel (SS) surface layer‐by‐layer in weak alkaline solution was reported. Field emission scanning electron microscope equipped with energy dispersive spectrometer, atomic force microscope, and X‐ray photoelectron spectroscopy were utilized to analyze the surface morphology and chemical composition of the modified SS. The results demonstrated that the surface of SS was coated with polydopamine (PDA) and Cu NPs successfully. The robustness assay of the Cu NPs surface demonstrated that most Cu NPs had bound on the surface of the stainless steel firmly. Antimicrobial assays showed that modified surface possessed the ability of resistance of Escherichia coli and Staphylococcus aureus to an effectiveness of 92.1% and 80.4%, respectively. The presence of copper offers the coatings' excellent capability to inhibit effectively the adhesion of marine diatom Phaeodactylum tricornutum to an effectiveness of 98.15%. This strategy exhibited a realistic paradigm for further improving the antifouling performances of hull surfaces.